Highly Sensitive Measurement of Bioelectric Potentials by Boron-Doped Diamond Electrodes for Plant Monitoring. (16th August 2016) - Ochiai, Tsuyoshi; Tago, Shoko; Hayashi, Mio; Fujishima, Akira
Abstract : A sensitive plant monitoring system for the detection of plant bioelectric potentials using boron-doped diamond (BDD) electrodes is presented. For sensor electrodes, commercially available BDD, Ag, Ag/AgCl, and Pt plate electrodes were used. This approach was tested on a hybrid species in the genus Opuntia (potted) and three different trees (ground-planted) in different locations in Japan. For the Opuntia, bioelectric potential changes were artificially induced by the surface potential using fingers. Substantial changes in bioelectric potentials were detected through all electrodes during finger touching on the potted Opuntia hybrid plant surfaces. However, the BDD electrodes were several times more sensitive to bioelectric potential changes compared to the other electrodes. For ground-planted trees, it was similarly found that both BDD and Pt electrodes detected bioelectric potential changes induced by altering environmental factors for multiple months. BDD electrodes were five to ten times more sensitive in this detection than Pt electrodes.